Simulation of breach outflow for earthfill dam - Razad A.Z.A.; Muda R.S.; Sidek L.M.; Azia I.S.A.; Mansor F.H.; Yalit R. (Institute of Physics Publishing, 2023)
Dams have been built for many reasons such as irrigation, hydropower, flood mitigation, and water supply to support development for the benefit of human. However, the huge amount of water stored behind the dam can seriously pose adverse impacts to the downstream community should it be released due to unwanted dam break event. To minimise the potential loss of lives and property damages, a workable Emergency Response Plan is required to be developed. As part of a responsible dam owner and operator, TNB initiated a study on dam breach modelling for Cameron Highlands Hydroelectric Scheme to simulate the potential dam breach for Jor Dam. Prediction of dam breach parameters using the empirical equations of Froehlich and Macdonal-Langridge-Monopolis formed the basis of the modelling, coupled with MIKE 11 software to obtain the breach outflow due to Probable Maximum Flood (PMF). This paper will therefore discuss the model setup, simulation procedure and comparison of the prediction with existing equations. Published under licence by IOP Publishing Ltd.